Interventional Echocardiography of the MV: What the Interventionalist Wants to Know. (March 2019) - Mitrev, Ludmil; Desai, Nayan; Awad, Ahmed; Sabir, Sajjad
The past 2 decades have seen a proliferation of transcatheter mitral valve (MV) therapies, which are less invasive and distinct from surgical MV repair or replacement. The commonly used MV transcatheter therapies include (1) percutaneous mitral balloon commissurotomy (PMBC) for rheumatic mitral stenosis; (2) edge-to-edge repair with the MitraClip for mitral regurgitation; (3) valve-in-valve implantation in bioprosthetic MV, native MV, or mitral ring; and (4) closure of paravalvular leaks (PVLs). This article will focus on the use of echocardiography in the diagnosis, patient selection, procedural guidance, and postprocedural follow-up for PMBC, with notes on the role of transesophageal echocardiography in transcatheter interventions for prosthetic valve degeneration and PVL closure.